Bolt assessment of wind turbine hub using nonlinear ultrasound methods. Issue 2 (April 2021) - Fierro, Gian Piero Malfense; Meo, Michele
This work evaluates various nonlinear ultrasound methods for in situ structural health monitoring of the loosened state of a four-bolt structure found on large-scale wind turbines. The aim was assessment of a four bolted structure with only two piezoelectric sensors, and determination of individual bolt loosened and the extent of loosening. Nonlinear ultrasound methods have been shown to have advantages over linear methods in terms of sensitivity, although the detection accuracy and robustness of these methods can be highly dependent on correct frequency selection. Thus, a frequency selection process based on the modal response of the structure is suggested for determination of bolt-specific frequencies, which was then used to evaluate the individual bolt loosened state. Two nonlinear ultrasound techniques were used to evaluate the bolted structure: the second- and third-order nonlinearity parameters and a nonlinear acoustic moment's method. The modal response method used for frequency selection was able to determine specific bolt frequencies based on surface and bolt velocities. Nonlinear evaluation at these frequencies showed that specific frequencies related to individual bolts, and as the bolts loosened there was a clear increase in the production of nonlinearities. Thus, the loosened status of individual bolts could be tracked using specific pre-identified frequencies.